Navigating pressure and connection: goal orientation, coach-athlete relationships, and burnout among Chinese collegiate athletes—a mixed-methods study - Le Wang; Hongye Lian (Frontiers in Psychology, 2025)
IntroductionCompetitive sport often imposes significant physical and psychological stress, making athlete burnout a primary concern. This mixed-methods study investigated the interplay of goal orientation, coach-athlete relationship (CAR) quality, and athlete burnout among Chinese collegiate athletes, considering unique cultural and systemic pressures.MethodsA sequential explanatory mixed-methods design was employed. The quantitative phase surveyed 346 athletes (Mage = 20.6 years) across five Chinese provinces using the TEOSQ (Task and Ego Orientation in Sport Questionnaire), CART-Q (Coach-Athlete Relationship Questionnaire), and RED-A (Reduced Exhaustion Depression and Reduced Accomplishment Scale). Data were analyzed using hierarchical regression. The qualitative phase involved semi-structured interviews with a purposive subsample of 28 diverse athletes, which underwent thematic analysis.ResultsQuantitative findings indicated that task orientation, CAR closeness, and complementarity were significant negative predictors of all burnout dimensions (p < 0.05). Ego orientation uniquely predicted higher cynicism (β = 0.15, p = 0.005). Significant interactions were observed: high closeness was associated with a weaker positive link between ego orientation and cynicism, and high complementarity was associated with an enhanced protective effect of task orientation on reduced accomplishment. CAR commitment did not emerge as a unique predictive factor. Qualitative themes elaborated on these findings, highlighting how performance pressures were associated with goal orientation (e.g., ego orientation linked to cynicism via perceived system barriers) and the importance of specific functional CAR aspects (e.g., complementarity fostering competence, closeness associated with buffering life stress). Interpretations of hardship (specifically “chī kǔ”) also related to task focus and its protective role.DiscussionThe findings underscore that athlete burnout in this context is shaped by motivational orientations and specific relational dynamics within unique cultural and systemic pressures. This suggests that effective interventions should target both individual (e.g., promoting task orientation) and relational factors (e.g., enhancing CAR closeness and complementarity).